Barriers to Retail Competition and Prices : Evidence From Spain - Hoffmaister, Willy (Washington, D.C. : International Monetary Fund, 2006)
Why do prices in Spain's regions fail to converge? The prime suspects for this puzzling result are differences in regional barriers to entry in retail distribution. This paper develops a Cournot-Nash model of imperfect competition to illustrate the effect of barriers on prices. A unique data set-derived from an extensive analysis of competition policies in Spain- provides evidence that barriers to entry increase regional prices. The evidence also suggests that, consistent with the model's predictions, barriers to entry raise prices up to a point, and thus indicate that barriers have a threshold effect on prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Spain